A Study into the Electrochemical Behavior of Nano Antibiotics as A Promising Treatment for Helicobacter Pylori Infection by Cyclic Voltammetry - Sarah Abbas Hussein Al-saeed; Muhammed Mizher Radhi; Zuhair Numan Hamed (Journal of Techniques, 2022)
The helicobacter-pylori (H.pylori) bacteria that infects the digestive system is one of the bacteria that is intractable in routine treatments with antibiotics, as it has been studied using nano-antibiotics studied by the electrochemical behavior of three Nano antibiotics. The study aims to identify the extent of the effect of micro-antibiotics on the composition of the blood serum medium by electrochemical analysis using the cyclic voltammetric method and to compare it with nano-antibiotics. Three Nano-antibiotics such as Amoxicillin NPs, Azithromycin NPs, and Metronidazole NPs, and the mixture of the three nanoparticles as Nano-Kit were investigated in blood serum medium utilizing cyclic voltammetry methods by a glass carbonic electrode (GCE). The three nanoparticles in antibiotics were prepared by converting the micro antibiotic with a lyophilizer technique and characterization by field emission scanning electron microscopy (FESEM) with all antibiotics in Nano size. The results showed that all Nano compounds act as an antioxidant antibiotic in the blood serum medium. The study also included the electrochemical characterization of the Nano-kit of the mixture for the three Nano-biotics to prove anti-oxidative stress. It was found that the three nano-biotics have reduced current peaks without any oxidation peaks. The three nano-antibiotics can be an excellent treatment to eradicate H. pylori infection permanently. Therefore, the results of this research can be adapted to use the nano-kit of the mixture in the appropriate treatment of H.pylori infection.